User Experience Analytics pada Sistem Informasi Politeknik Negeri Ujung Pandang - HM, Nurfaida; Tungadi, Eddy; Syamsuddin, Irfan (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2022)
The Ujung Pandang State Polytechnic (PNUP) manages several departments, consisting of the Department of Electrical Engineering, the Department of Machinery, the Department of Civil, the Department of Chemistry, the Department of Accounting, and the Department of Commerce Administration. In managing how many significant programs, PNUP requires a quality information system to support academic activities by evaluating the system's quality that has been implemented. The PNUP Information System with the URL address https://.www.poliupg.ac.id/ has never been evaluated, where there are several complaints from students and admins regarding obstacles to using the information system. Complaints about the information system's use prompted researchers to research the quality of the PNUP information system. Therefore, the User Experience was analysed from the usability aspect, which was tested with several tools, namely Woorank, SEOquake, PageSpeed and using the SUS method. Testing with the usability aspect approach was carried out on the information system at PNUP. The test results using several tools, namely Woorank, got a score of 78. It was considered suitable for facilitating searches on search engines. Page Speed scored 67 for desktop use and 28 for mobile use. It was considered very bad in loading website pages which were considered to disturb user satisfaction and using the SUS method, with 180 respondents getting a score of 58.65, which is considered usable and has the potential to reduce visitors to the PNUP information system. It can be judged that the PNUP information system has not met the usability aspect.